Molecular pharmacokinetic mechanism of quercetin-encapsulated polymeric micelles in alleviating cisplatin-induced nephrotoxicity and enhancing antineoplastic effects - Tangna Hao; Tangna Hao; Tangna Hao; Xiaokui Huo; Zhen Li; Changyuan Wang; Changyuan Wang; Sha Wu; Anni Song; Fengyu Zhang; Kexin Liu; Kexin Liu; et al. (Frontiers in Pharmacology)
IntroductionCisplatin (DDP), a platinum-based chemotherapy drug, shows broad antineoplastic activity, however, its clinical use is limited by dose-dependent nephrotoxicity, a major challenge in cancer therapy. The purpose of this study was to investigate the mechanism by which quercetin-polyethylene glycol-polycaprolactone (Que-PEG-PCL) micelles simultaneously enhance the cytotoxicity of DDP against cancer cells and reduce its nephrotoxicity.MethodsRodent models and HEK293 cells were used to evaluate the renoprotective effects of Que-PEG-PCL micelles. Pharmacokinetics focused on OCT2-mediated renal DDP disposition. Antitumor activity was assessed in CT26 cells and syngeneic tumors. Key assessments included oxidative stress, apoptosis, renal markers, and histopathology.Results:Que-PEG-PCL reduced DDP-induced nephrotoxicity, lowering creatinine and BUN to 42% and 38%. It also reduced oxidative stress and improved antioxidant activity. DDP plasma exposure increased to 323%, with renal clearance reduced to 14%, due to OCT2 inhibition. In a CT26 syngeneic model, combination therapy inhibited tumor volume by 84% compared to control group.DiscussionQue-PEG-PCL enhanced DDP’s therapeutic window by limiting renal accumulation and promoting tumor cell apoptosis. This dual-action strategy provides a novel approach for improving the clinical efficacy of DDP-based cancer therapy.